Degradation of tetracycline in a schorl/H2O2 system: Proposed mechanism and intermediates. (July 2018) - Zhang, Yihan; Shi, Jing; Xu, Zhengwen; Chen, Yue; Song, Duanmei
Abstract: Schorl could perform as an extremely promising catalyst for decomposing tetracycline hydrochloride (TC) due to its high degradation efficiency, low cost, chemical stability, easy recovery and repeatable utilization. Comparisons of TC degradation indifferent systems showed that schorl/H2 O2 system exhibited the optimum pollutant elimination and TOC removal efficiencies. Kinetics and possible mechanisms of TC degradation were clarified. The OH generated on the schorl surface and O2 − /HO2 were the main reactive species responsible for TC oxidation. Six possible intermediates were identified, and possible transform mechanisms and pathways were explored. Active radicals were inclined to attack the CC double bond, dimethylamino and phenolic moieties of TC molecular. The principal intermediate products were generated through N-demethylation, oxidation and rearrangement. Highlights: Catalytic properties of schorl were explored. Schorl/H2 O2 system showed remarkable performance in TC removal. Six possible intermediates were identified by LC–MS/MS.